Research Progress About Glioma Stem Cells in the Immune Microenvironment of Glioma - Li, Xiangyu; Liu, Ming; Zhao, Junfeng; Ren, Tong; Yan, Xin; Zhang, Lijun; Wang, Xun (Frontiers in Pharmacology, 2021)
Gliomas are the most common primary tumors of the central nervous system. Due to the existence of the blood-brain barrier and its unique regional immune characteristics, the study of the immune microenvironment of gliomas is particularly important. Glioma stem cells are an important cause of initiating glioma, promoting tumor progression and leading to tumor recurrence. Immunotherapeutic strategies targeting glioma stem cells have become the focus of current research. This paper will focus on the research progress of glioma stem cells in the immune microenvironment of glioma to provide the basis for the immunotherapy of brain glioma.